Molecular and morphological data from Thoosidae in favour of the creation of a new suborder of Tetractinellida. Issue 5 (4th July 2018) - Carballo, JosÉ Luis; Bautista-Guerrero, Eric; CÁrdenas, Paco; Cruz-Barraza, Jose Antonio; Aguilar-Camacho, Jose Maria
Abstract : The Thoosidae (Porifera, Demospongiae, Tetractinellida) currently includes the genera Thoosa, Alectona, and Delectona . To this date, molecular data are only available for Alectona . In this study, the phylogenetic affinities of the genera Thoosa and Alectona have been investigated with the species T. mismalolli, T. calpulli, and T. purpurea from the Mexican Pacific using morphology and three molecular loci: the mitochondrial cytochrome oxidase subunit 1 (CO1 mtDNA), 28S rRNA (fragment D2), and 18S rRNA. Morphology and embryology showed that these genera are quite different from the rest of the tetractinellids because larvae of Alectona and Thoosa have unique features in sponges, such as the presence of monaxonic discs in Thoosa and tetraxonic discs in Alectona which disappear in the adult stages. A phylogenetic analysis using selected species from the order Tetractinellida revealed that Thoosa groups with Alectona thus confirming morphological studies. The peculiarities in spiculation and embryology of the Thoosa and Alectona larvae, which are markedly different from species belonging to the suborders Astrophorina and Spirophorina and their distant phylogenetic position (based on three molecular loci), suggest that Thoosidae could be placed in the new suborder Thoosina.